PENERAPAN METODE PEMBELAJARAN QUANTUM TIPE TEKNIK PETA KONSEP DALAM RANGKA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA - Cahyono, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study reviews the application of learning methods of quantum type of concept maps in order to improve the ability to think creatively and student learning outcomes on economic subjects in vocational Kubu Raya Development. The method used in this study is a research method True Experiment Experiment with the shape and the experimental design used is pretest - posttest control group design. The population in this study is a class XI student of SMK AKT Development amounted to 96 students with a sample of 64 students. The data collection tool in this study a test sheet and observation sheet. Data was analyzed using quantitative data analysis and descriptive statistics. The results showed that the application of quantum learning method in class experiment goes well. Application of quantum learning methods can enhance students' ability to think creatively on economic subjects in vocational Kubu Raya Development. Through t test, t known at 37.185 and Sig. (2-tailed) 0.000 (0.000 <0.005) showed an increase of quantum methods in creative thinking abilities.Keywords: Quantum Learning Method, Creative Thinking Skills, Learning Outcome